Pengaruh Trend Fashion terhadap Pertumbuhan Industri Tekstil terhadap Emisi Gas Rumah Kaca : (Studi Komparasi Indonesia Dan Vietnam) - Kadek Esa Pratiwi Ngurah Putri (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
The ever-changing and rapidly developing fashion trends have created a consumer culture among global society, driven by social media and digital marketing. Excessive consumption of clothing not only fulfills personal needs but also becomes an indicator of social status. As a result, the textile industry has experienced rapid growth, contributing significantly to the economy, especially in countries such as Indonesia and Vietnam. However, textile production uses energy sources that are not environmentally friendly, producing greenhouse gas emissions that have negative impacts on the environment, such as global warming and climate change. Indonesia and Vietnam, as one of the developing countries that rely on industry as a profitable sector, act as the largest contributors of emissions in Southeast Asia. Indonesia and Vietnam face major challenges in reducing environmental impacts while maintaining economic growth. Efforts to reduce greenhouse gas emissions are an important priority for long-term sustainability. The implementation of clear, firm and targeted regulations plays an important role in enforcing rules that can protect the environment from perpetrators of destruction by the industrial sector.